2014
DOI: 10.1517/17425247.2014.890588
|View full text |Cite
|
Sign up to set email alerts
|

Optimized PLGA nanoparticle platform for orally dosedtrans-resveratrol with enhanced bioavailability potential

Abstract: The studies, therefore, could provide another useful tool for successful development of t-RVT NPs and an in vivo approach to designate nanoparticulate system of t-RVT with distinctly improved bioavailability and to overcome enterohepatic recirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…68,175 PLGA-coated resveratrol nanoparticles enhance the bioavailability of resveratrol for up to 4 days in a rat model. 176 Their research group also studied sustained release of trans-resveratrol in vitro and found higher solubility and dissolubility of trans-resveratrol. 68,175,176 In addition, a combination of one or two nanosized bioactive compounds has multiple health beneficial effects for certain diseases, which further reduces the multiple drug load.…”
Section: Nanoresveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…68,175 PLGA-coated resveratrol nanoparticles enhance the bioavailability of resveratrol for up to 4 days in a rat model. 176 Their research group also studied sustained release of trans-resveratrol in vitro and found higher solubility and dissolubility of trans-resveratrol. 68,175,176 In addition, a combination of one or two nanosized bioactive compounds has multiple health beneficial effects for certain diseases, which further reduces the multiple drug load.…”
Section: Nanoresveratrolmentioning
confidence: 99%
“…176 Their research group also studied sustained release of trans-resveratrol in vitro and found higher solubility and dissolubility of trans-resveratrol. 68,175,176 In addition, a combination of one or two nanosized bioactive compounds has multiple health beneficial effects for certain diseases, which further reduces the multiple drug load. Curcumin and resveratrol encapsulated nanoliposomes have an antitumor effect against prostate cancer.…”
Section: Nanoresveratrolmentioning
confidence: 99%
“…However, there was no double peaks phenomenon in rats by administration of GNA-NS. As the literature reported, nanoparticulate drug delivery system can overcome the enterohepatic recirculation phenomena (Singh et al, 2014). For example, Hong et al (2014) prepared myricetin NS and the enterohepatic recirculation of myricetin crude drug in rats was subdued by administration of NS formulation.…”
Section: In Vivo Evaluation Of Gna-nsmentioning
confidence: 99%
“…Besides these, it undergoes rapid first-pass metabolism by CYP3A4 in the liver and suffers enterohepatic recirculation, eventually leading to a marked reduction in the drug's oral bioavailable fraction (almost zero) in humans and animals like rats, etc. (Amri et al 2012, Marier et al 2002, Singh and Pai 2014a, 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…All these formulations were able to increase the solubility and/or dissolution performance only. We recently reported the use of PLGA nanoparticles for improvement in absorption and subsequent oral bioavailability of t-RVT (Singh and Pai 2014a). Amri et al (2013) reported the self-emulsifying resveratrol drug delivery system, wherein they were able to achieve both the uptake by endothelial cells and improved protection against oxidative stress-mediated death.…”
Section: Introductionmentioning
confidence: 99%